THE PENGARUH PERMAINAN EKSPLORASI SAINS TERHADAP PERILAKU SAINTIFIK ANAK USIA DINI - Ignatia Imelda Fitriani; Sophia Oktavia; Dhea Amalia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2022)
T The Early Childhood Education curriculum emphasizes scientific learning patterns in which children are allowed to observe directly, ask questions, gather information, reason and recommunicate again what they have learned. This learning experience through various sensory senses makes children absorb and remember information faster. The purpose of the study was to determine the effect of science games on scientific behaviour in early childhood. The research conducted at the Stella Sophie Kindergarten, Palangka Raya involved 21 childrens as research subjects. Data collection throughout saw the dynamics of changes in children's scientific behaviour as an intervention from this science game exploration activity. The data collected three times before and during the stimulation of science game exploration activities. Data were analyzed using the analysis of variance. The results showed the differences in children's scientific behaviour before and after playing science exploration games. Science games have been shown improve early childhood scientific behaviour significantly